PENGARUH PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IIS SMA PEMBANGUNAN LABORATORIUM UNP - Andriani, Andriani (Jurnal Edukasi dan Penelitian Matematika, 2023)
The ability to understand mathematical concepts of students at UNP Laboratory Development High School is still not optimal. One of the efforts to improve the ability to understand students' mathematical concepts is to apply Contextual Teaching and Learning in learning mathematics. This study aims to find out whether the ability to understand mathematical concepts of students whose learning uses the Contextual Teaching and Learning (CTL) model is better than the ability to understand concepts using direct learning in class XI IIS SMA Development Laboratory UNP. This study uses a type of quasi-experimental research. The population in this study were all students in class XI IIS SMA Development Laboratory UNP for the academic year 2022/2023. Sampling was carried out using a simple random sampling technique. After carrying out the sampling steps, class XI IIS 1 was selected as the experimental class and class XI IIS 2 as the control class. The test instrument used is a test of the ability to understand mathematical concepts. The results showed that the students' ability to understand mathematical concepts in the class that applied the CTL model was better than the ability to understand concepts in the class that applied direct learning in class XI IIS SMA Pembangunan Laboratory UNP. Thus, it can be concluded that there is an influence from the application of the CTL learning model on students' understanding of mathematical conceptsKeywords– Concept Understanding, Contextual Teaching and Learning Model, Direct Learning Model